Expansion The Meaning Of Principle Lex Specialis Derogat Lex Generalis - Itok Dwi Kurniawan (PT. Gudang Pustaka Cendekia, 2023)
The aim of writing this article is to determine the expansion of the meaning of the principle of lex specialis derogate legi generali which occurs in cases of same-sex sexual harassment. This research is normative legal research that uses a case approach and a conceptual approach. The legal materials used are primary legal materials and secondary legal materials. The technique for collecting and analyzing legal materials used in writing this article is literature study. The result of this research is that the principle of lex specialis derogate legi generali, when implemented in certain cases, can have an expanded meaning. The first meaning is that specific laws override general laws, while the expansion of the intended meaning in a particular case can be interpreted as the textual suitability of the law and the case that occurred.